Effects of a 6-Week Faroese Chain Dance Programme on Postural Balance, Physical Function, and Health Profile in Elderly Subjects: A Pilot Study - Hofgaard, Jóhan; Mohr, Magni; Ermidis, G. (BioMed research international, 2019)
The present pilot study investigates the impact of a Faroese chain dance intervention on health profile, mobility, and postural balance in elderly subjects. Healthy elderly subjects (n=27; age 75 ± 5 yrs) were randomised into an intervention group (IG) and a control group (CG). IG performed twice-weekly sessions of Faroese chain dance over 6 weeks. Dancing sessions lasted 30 min in the initial 3 weeks and 45 min in the final 3 weeks. Health profile was determined before and after intervention by measuring blood pressure, resting heart rate, muscle mass, and body fat content. Postural balance was evaluated using the Berg Balance Scale (BBS) and Fullerton Advanced Balance Scale (FAB) tests, while mobility was assessed using the Short Physical Performance Battery (SPPB), the Timed Up & Go (TUG) test, the 6-min walk test, and the 30-s sit-to-stand test. Systolic and diastolic blood pressure were lowered (9 ± 6 and 6 ± 3 mmHg, respectively) in IG, with a tendency (P=0.07) for a greater change score than in CG. Mean arterial pressure declined (P<0.05) by 7 ± 3 mmHg in IG, which tended (P=0.09) to be greater than in CG. IG improved (P<0.05) on BBS and FAB scores by 3.6 ± 2.1% and 15.8 ± 8.3%, with the change score for FAB being greater (P<0.05) than in CG (0.3 ± 1.6). Moreover, the postintervention SPPB score was improved (P<0.05) more in IG (13.9 ± 7.4%) compared to CG, while performance in the 30-s sit-to-stand, 6-min walk, and TUG tests improved (4–15%; P<0.05) in IG only. Body fat content was reduced (P<0.05) from 36.3 ± 2.8% to 34.8 ± 2.8% in IG, with no between-group differences and no change in CG (34.1 ± 2.8% to 33.7 ± 3.1%). In conclusion, a 6-week Faroese chain dance programme lowers blood pressure and improves postural balance and physical function in elderly.